Local Economic Conditions and the Nature of New Housing Supply - Christian A.L. Hilber; Jan Rouwendal; Wouter Vermeulen (Tinbergen Institute, 2014)
We present a modified open monocentric city model that assumes that land is available for conversion into new housing throughout the city. The model predicts that positive local income shocks (i) increase the citys share of multi-family housing in new construction and (ii) lead to the construction of smaller units. We exploit the metro area samples of the American Housing Survey from 1984 to 2004 and find support for both predictions. We confirm that the adjustment process is driven by migration and is hindered by strict local land use control. Our findings imply that tight regulation may hamper metro area level labor market adjustment to positive economic shocks not only through limits on the quantity of newly supplied units but also by constraining their type to single-family houses and larger units that may be less suitable for would-be-migrants.
Keywords: R11; R21; R31; R52; 330; Local economic conditions; open monocentric city model; land conversion; housing supply; housing type; housing consumption; land use regulation; migration